Etnobotani Tikung Masyarakat Melayu Dusun Batu Rawan Kabupaten Kapuas Hulu dalam Budidaya Madu Secara Tradisional - Ayu, Masha; Lovadi, Irwan; Gusmalawati, Dwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Wild Honey is produced directly from the hives of Apis dorsata bees or wild bees that live in forest areas. Wild Honey is produced through traditional methods that utilize plants and are not livestock. Plants that are utilized in the form of plant wood as artificial nests called tikung and flowers from bee food trees. The purpose of this study was to determine the types of plants as tikung wood and bee food trees and document the knowledge of traditional honey farmers about the ethnoecology of Batu Rawan Hamlet, Kapuas Hulu Regency. This study used purposive sampling method in determining respondents and 15 respondents were obtained, then continued with semi-structured interviews. Data analysis was conducted with citation frequency. The results showed that there were 5 species of tikung wood and 15 species of bee food trees belonging to 12 families. Fagraea fragrans, Shorea belangaran, Litsea resinosa, Gluta renghas, Shorea sp., are plant species used as tikung wood trees, the dominant species reported by respondents is Litsea resinosa which is 93.3%. Mesua hexapetala, Syzygium claviflorum, Barringtonia acutangula, Ternstroemia sp., Carallia brachiata, Teysmanniodendron sarawakanum, Syzygium sp., Gomphia serrata, Eugenia sp., Syzygium inophyllum, Timonius flavescens, Ixora mentangis, Syzygium attenuatum, Memecylon edule, Crudia teysmannii are plant species used as bee fodder trees, bee fodder tree species reported dominantly by respondents are Barringtonia acutangula species which is 100%.